2000
DOI: 10.1097/00004872-200018020-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cicletanine reverses vasoconstriction induced by the endogenous sodium pump ligand, marinobufagenin, via a protein kinase C dependent mechanism

Abstract: Cicletanine antagonizes vasoconstriction induced by Na/K-ATPase inhibition via a PKC-dependent mechanism that does not involve inhibition of cyclic GMP phosphodiesterase (cGMP-PDE). This mechanism of action may be relevant to the greater potency of cicletanine in salt-sensitive hypertension in which plasma levels of endogenous digitalis-like cardiotonic steroids are elevated. Our findings also suggest that PKC is an important factor for cardiotonic steroid-Na/K-ATPase interactions on the vascular tone, and is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
(34 reference statements)
1
12
0
Order By: Relevance
“…Our recent results, indeed, demonstrate that the vasodilatory effect of cicletanine is PKC dependent in human mesenteric arteries precontracted with MBG. 11 In the present study, cicletanine treatment of DS was associated with an improvement of renal function. Previous studies also documented that cicletanine, even at subdepressor doses, exhibited renal-protective effects.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Our recent results, indeed, demonstrate that the vasodilatory effect of cicletanine is PKC dependent in human mesenteric arteries precontracted with MBG. 11 In the present study, cicletanine treatment of DS was associated with an improvement of renal function. Previous studies also documented that cicletanine, even at subdepressor doses, exhibited renal-protective effects.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, we have demonstrated that, indeed, cicletanine does reverse the MBG-induced vasoconstriction and NKA inhibition by way of a PKC-sensitive mechanism. 11 This effect of cicletanine was blocked by phorbol ester and was, therefore, modulated by phorbolsensitive PKC isoforms, such as ␤2 and ␦. Our present results show that although in vivo cicletanine treatment did not affect the increased expression of ␣-1 NKA protein in the myocardium effected by the high-NaCl diet, it reduced the sensitivity of LV sarcolemmal NKA to MBG and prevented the reduction in sarcolemmal NKA activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 This vasorelaxant effect of cicletanine did not occur in the presence of PDA. Thus, taken together, our present and previous results suggest that PKC activation potentiates, whereas PKC inhibition reverses both the NKA inhibitory and vasoconstrictor effects of MBG, and that PKC phosphorylation of the ␣ 1 -subunit of the sodium pump, at least in part, underlies this phenomenon.…”
Section: Discussionmentioning
confidence: 89%